Effects of tongue cleaning on plaque and salivary mutans streptococci levels: A randomized controlled trial - Kochiyil Chacko Jacob; R Yashoda; Manjunath P Puranik; Asima Bano (Wolters Kluwer Medknow Publications, 2015)
Introduction: Tongue cleaning has been shown to be effective in preventing plaque formation and reducing oral mutans streptococci (MS) when used in combination with other oral hygiene procedures. However, correlation between MS counts and plaque levels remains to be demonstrated. Aim: To evaluate the effect of tongue scraping and tongue brushing on salivary MS and plaque levels. Materials and Methods: A triple-blind three arm randomized controlled parallel-group trial was carried out among 54, 12-15-year-old boys in a residential school in Bengaluru city. The study participants were randomly allocated into Group A (toothbrushing and tongue scraping; n = 19), Group B (toothbrushing and tongue brushing; n = 18) and Group C (only toothbrushing; n = 17). The clinical procedure included a collection of saliva and recording of plaque index at baseline, 10th and 21st day. Salivary MS counts were determined using mitis salivarius bacitracin Agar media. ANOVA, Wilcoxon's signed-rank sum test, Mann-Whitney U-test and Spearman's correlation test were performed on log-transformed CFU/mL of MS. Results: The tongue scraping and tongue brushing groups showed statistically significant reductions in salivary MS counts after 10 days (4.76 ± 0.54) (4.79 ± 0.44) and 21 days (4.50 ± 0.44) (4.41 ± 0.57) respectively when performed along with toothbrushing. However, differences between the interventions were not statistically significant. Furthermore, there was no statistically significant reduction in plaque levels after 10 and 21 days. Conclusions: Tongue scraping and tongue brushing were equally effective in reducing salivary MS counts when used in combination with toothbrushing, however, their effect on reducing plaque levels was not significant. Hence, tongue cleaning is recommended as an adjunct to toothbrushing.